X-ray tomography measurements of power-law cluster size distributions for the nonwetting phase in sandstones. - Iglauer, Stefan; Favretto, S.; Spinelli, G.; Schena, G.; Blunt, M. (The American Physical Society, 2010)
Three-dimensional images of sandstones containing residual nonwetting phase were obtained using synchrotron x-ray tomography with a resolution of approximately 9 µm. We determined the size distribution of disconnected nonwetting phase clusters (ganglia); the number of ganglia of size s is N(s)~s(-t) with t=2.05 . The vast majority of the residual phase was contained in large clusters, spanning many pores. This result implies that we have clusters of all sizes providing a huge surface area for geochemical reactions and dissolution while allowing mobilization of the residual phase during improved oil recovery in hydrocarbon reservoirs and carbon dioxide storage in aquifers.